Causal effects of inflammatory cytokines on hemangioma mediated by blood metabolites: a two-step Mendelian randomization study - Yu, Fan; You, Yuanhe; Zhao, Zhiyang; Tian, Zhuowei; Wang, Yanan; Xiao, Meng; Du, Zhong (Journal of Medical Biochemistry, 2025)
Background: Hemangioma is the most prevalent infantile vascular tumor. The state of inflammation and metabolism may contribute to the occurrence and development of hemangioma, but their causal relationships have not been clearly elucidated. In this study, via Mendelian randomization (MR) analysis, we aimed to investigate the causal effect of inflammatory cytokines and blood metabolites on hemangioma, and to explore the potential mediating role of metabolites. Methods: Applying large-scale genome-wide association studies (GWAS) dataset, we applied two-sample MR to infer causal relationships among 91 inflammatory cytokines, 1091 blood metabolites and 309 metabolite ratios，and hemangioma. In addition, a two-step MR was used to assess the potential mediating role of metabolites. Functional enrichment was also performed to explore the biological pathways involved. Results: 9 cytokines exhibited significant causal effects on hemangioma. Cytokines such as CCL20, IFN-γ, Eotaxin and TRANCE were associated with an increased risk, while IL12B, CXCL11, TGF-α, OSM and IL17A were inversely associated. Additionally, 52 blood metabolites and metabolite-ratios were discovered to have causal effects on hemangioma. 18 metabolites and metabolite-ratios were associated with an elevated risk of hemangioma, whereas 34 metabolites and metabolite-ratios appeared to be protective factors. Mediation analysis further identified specific metabolites, such as Gamma-glutamylvaline, as mediators in cytokine-hemangioma pathways, suggesting that they might modulate cytokine-driven tumorigenesis. Conclusion: As the first MR study focused on hemangioma, we identified key cytokines and metabolites which might exert a causal effect on hemangioma, with several metabolites functioning as intermediators in cytokine-induced tumorigenesis process. The complex interaction between inflammation and metabolism in hemangioma was revealed, laying a foundation for future studies to explore potential targeted treatments.